Stress-deformed state and strength of a locally heterogeneous electrically conductive layer - Маркович, Б. М.; Сеник, Ю. А.; Ноджак, Л. С.; Markovych, B. M.; Senyk, Y. A.; Nodzhak, L. S. (Видавництво Львівської політехніки, 2022)
Представлено ключову систему рівнянь моделі твердого тіла із врахуванням структурної неоднорідності матеріалу та шорсткості реальної поверхні, яку застосовано до вивчення взаємозв’язаних полів у необмеженому гетерогенному електропровідному шарі. Розглянуто вплив врахування залежностей від густини локальних модуля Юнга та коефіцієнта Пуассона на розмірні ефекти поверхневих напружень в шарі та межу його міцності.

The key system of equations of the solid body model is presented, taking into account the structural heterogeneity of the material and the roughness of the real surface, which is applied to the study of interconnected fields in an unbounded heterogeneous conductive layer. The effect of taking into account the dependences on the density of local Young's modulus and Poisson's ratio on the size effects of surface stresses in the layer and its strength limit is considered.
Напружено-деформований стан та міцність локально неоднорідного електропровідного шару
Keywords: електропровідне тіло; напруження; модулі пружності; розмірні ефекти; міцність; electroconductive body; stresses; modulus of elasticity; size effects; strength